Ants - Philip G. Koehler; Roberto M. Pereira; Faith M. Oi (EDIS, 2007)
Revised! ENY-203, an 8-page illustrated fact sheet by P. G. Koehler, R. M. Pereira, and F. M. Oi, provides information about ants in Florida, identification, biology, food preferences, and control. This revision trims off 20 pages of tables listing pesticides registered in Florida for homeowner and commercial use and expands information on prevention. Includes references. Published by the UF Department of Entomology and Nematology, August 2007.